Uma estratégia ativa para detecção de ilhamento em geradores fotovoltaicos por meio de injeção de sinais de teste - CARVALHO, Fransérgio Martins (Universidade Federal do Pará, 2017)
In this paper, is made a study of a active technique for detection of islanding that is proper for application in Grid-Connected Photovoltaic System (GCPS). The technique is based on injection of testing signals which affect negative-sequence of voltage after islanding case. Definitions and explanations are presented about power distributing system and about the elements which belong to Distributed Generation (DG). Standards about inverter’s function and about model of photovoltaic cell are presented. Details of islanding concept and its Non-Detection Zone (NDZ) as well as main current techniques for its detection are exhibited. It is shown the sequence-negative technique. Some instrumental applications related to negative-sequence measurement, sinusoidal inverter and PLL are developed. Models are designed to accomplish the injection and measurement of negative-sequence through VSI: controller and filter. Simulations were made to detect islanding under ordinary conditions of GCPS: irradiance variation and shading of photovoltaic cell; and under ordinary conditions of a power distribution system: charging variation and unbalanced charge. At last, the applied method performance is validated and compared.